TINGKAT KEPERCAYAAN DIRI TERHADAP KEMAMPUAN DRIBBLING PADA PESERTA EKSTRAKURIKULER FUTSAL SISWA SMPN 4 AMUNTAI - Wahyudi, Muhammad Ibda; Ramadhan Arifin; Lazuardy Akbar Fauzan (Universitas Negeri Medan, 2024)
This study aims to analyze the level of self-confidence among students participating in futsal extracurricular activities at SMPN 4 Amuntai and examine its relationship with dribbling skill performance. The study employs a descriptive quantitative approach, involving 16 students who completed a Likert scale questionnaire consisting of 20 statement items about self-confidence, and subsequently took a standardized dribbling skill test. The total score obtained from the self-confidence questionnaire reached 807 out of a maximum possible score of 1600, resulting in an achievement percentage of 50.44%—classified as